Achievement of Possibly Maximum Photosynthetic Performances for Multi-Primary Laser Lighting for Indoor Farming - Bingui Lv; Mingkai Huang; Meixue Chen; Liyue Xu; Lihong Lian; Huanting Chen; Yangyu Yao; Jingxuan Sun; Yixuan Lu; Xinqin Liao; Zhong Chen; Ziquan Guo (IEEE Photonics Journal, 2023)
The artificial lighting based on multiple-primary light-emitting diodes (LEDs) or multiple-primary laser diodes (LDs) makes the diversity of colors by freely and simply adjusting the emission spectra of rays from these semiconductor devices. It brings the possibility that the artificial lighting matches well with the photosynthetic spectral sensitivity curves of most plants including vegetables and fruits on the earth. Via reasonably designing the spectral components of artificial lighting sources based on intelligent optimization algorithms such as genetic algorithm (GA), one can readily achieve the maximum photosynthetic luminous efficacy of radiation (PLER), at the same time with good color rendering properties. In this regard, the IES-TM-30 scores (color fidelity index Rf and color gamut index Rg) suggested by Illuminating Engineering Society of North America (IES) is employed for evaluating the color rendering performances of artificial lighting sources besides the well-known standardized color rendering index (CRI, Ra). Compared with LEDs, the LDs are free from the so-called “efficiency droop” phenomena, thus have shown great superiority over the LEDs. Therefore, the aim of this work is to explore the maximum PLER of multiple-primary laser lighting while ensuring relatively good color rendering properties. Hope that the achieved results could provide a useful guidance for the quick development of this field.